CLIMATE DEVELOPMENT AND CORPORATE ORGANIZATIONAL COMMUNICATION SATISFACTION TOWARD EMPLOYEE PERFORMANCE IMPROVEMENT - Muya Syaroh Iwanda Lubis; Nurhayati Nurhayati; Elda Elda (Universitas Dharmawangsa Medan, 2022)
ABSTRACTEmployee performance in a company or agency organization must be demanded because with performance, existing human resources will have innovations related to improving quality as a symbol Because productivity is the result of a continuous process that begins with the operationalization of a company or an institution, consideration of human capital has a special place in the organization of a company or an institution. the use of effective communication is allegedly able to create communication satisfaction among employees because it reduces the distortion of conveying information that is not necessary. So that when examined in more depth, the organizational communication climate in the company can create organizational communication satisfaction, namely being able to use effective communication which will later act as an instrument in improving employee performance in maximizing their potential in the development and progress of the company.Keywords: Climate Development, Corporate Organizational, Communication Employee